Peranan Psikologi Perkembangan Islam Berwawasan Multikultural terhadap Kondisi Remaja di SMP Nasional Plus Pelita Insani - Miftahul Huda; Dewi Desmawati; Suharno Suharno; Rapiudin Rapiudin; Suseno Pranoto (Student Scientific Creativity Journal, 2026)
Adolescence is a critical period of psychological, social, and religious identity formation, particularly in schools with multicultural and multireligious student populations such as SMP Nasional Plus Pelita Insani. This study examines the role of Islamic developmental psychology with a multicultural perspective in shaping adolescents' character, tolerance, and religious identity within a diverse school environment. Using a qualitative descriptive approach with the STAR method (Situation, Challenge, Action, Reflection), this study analyzes the situation faced by adolescents in a multicultural school setting, the psychosocial and religious challenges that arise, the pedagogical actions taken by educators grounded in Islamic developmental psychology, and the reflective outcomes of those actions. The findings indicate that an approach integrating Islamic developmental psychology with multicultural insight can strengthen adolescents' religious moderation, empathy, and social adjustment, while reducing the potential for identity conflict, intolerance, and social exclusion among students of different cultural and religious backgrounds. The study recommends that Islamic Religious Education teachers adopt a developmentally sensitive and culturally responsive pedagogical model to optimize adolescents' psychological and spiritual growth in multicultural school settings.